The Effect of New Formula Liquid Organic Fertilizer and Water Sprinkling on Urban Portable Rice Fields - Sofyan Samad; Shubzan A. Mahmud; Hayun Abdullah; Sugeng Haryanto; Radhiatunnisa S. Samad (Green Publisher Indonesia, 2021)
The spread of the corona virus is the impact of the community's household economy and the decline in community food security. Goals Growth and production of upland rice through the provision of a new formula liquid organic fertilizer (POC FB) in bucket media above the house to meet people's food during the covid-19 pandemic. Place in Gambesi from March to August 2020. Upland rice seed ingredients, new formula liquid organic fertilizer (POC FB). Treatment with 5 levels (FOC FB) with doses / pot as follows: 0 cc / liter of water (B0), 10 cc / liter of water (B1), 15 cc / liter of water (B2), 20 cc / liter of water (B3) , 2 5 cc / liter of water (B4), 30 cc / liter of water (B5). Lack of water as a dissolved material and the availability of small bucket media or upland rice plants can affect upland rice growth and yield variables. The results of the analysis of variance showed a new formula liquid organic fertilizer at a dose of 30 cc / liter of water / bucket (B5). yielded 70 cm high and 42 tillers, 44 cm panicles and 39 g dry weight when compared with other treatments. POC FB is a liquid organic fertilizer that provides macro and micro elements so that it accelerates the growth, development, height, tiller, panicle and harvest weight of upland rice plants.